The relationship between technological innovation, human capital and civil liberties in advancing economic complexity and sustainable growth - Fan, Yuemin; Jackson, Ana (Frontiers in Environmental Science, 2025)
IntroductionTechnological innovations that drive the development of new goods and processes play a crucial role in achieving sustainable development goals. However, reliance on natural resource rents may impede the pace of technological advancement. This study examines the relationship between technological innovation, economic complexity, GDP, civil liberties, human capital, and natural resource rents in G-20 countries using panel data from 1990 to 2022.MethodsTo analyze these relationships, we employ the augmented mean group (AMG) and common correlated effects mean group (CCEMG) models, incorporating structural breaks within cointegration approaches.ResultsThe findings indicate that a country’s reliance on natural resources does not necessarily hinder its ability to foster technological innovation. Additionally, higher GDP per capita is shown to significantly enhance innovation across the aggregate panel. Cointegration tests confirm a long-term relationship among the variables and reveal the presence of structural breaks, highlighting the complexity of these dynamics. Both the AMG and CCEMG models identify GDP as a strong predictor of innovation, with technological advancements showing particular significance in AMG estimation. However, the effects of natural resources, human capital, and civil liberties appear limited in both models, suggesting their impact may be context-dependent or influenced by other factors.DiscussionThe study underscores the importance of leveraging natural resource revenues to support economic diversification and technological innovation, both of which are critical for sustainable development. Policymakers should prioritize investments that foster economic complexity and innovation to ensure meeting long-term sustainable development goals (SDGs) and Paris Agreement requirements.